The physical drivers and observational tracers of CO-to-H2 conversion factor variations in nearby barred galaxy centers - Teng, Yu-Hsuan; Sandstrom, Karin M.; Sun, Jiayi; Gong, Munan; Bolatto, Alberto D.; Chiang, I.-Da; Leroy, Adam K.; Usero, Antonio; Glover, Simon; Klessen, Ralf S.; Liu, Daizhong; Querejeta, Miguel; et al. (The astrophysical journal, 2023)
The CO-to-H2 conversion factor (α CO) is central to measuring the amount and properties of molecular gas. It is known to vary with environmental conditions, and previous studies have revealed lower α CO in the centers of some barred galaxies on kiloparsec scales. To unveil the physical drivers of such variations, we obtained Atacama Large Millimeter/submillimeter Array bands (3), (6), and (7) observations toward the inner ∼2 kpc of NGC 3627 and NGC 4321 tracing 12CO, 13CO, and C18O lines on ∼100 pc scales. Our multiline modeling and Bayesian likelihood analysis of these data sets reveal variations of molecular gas density, temperature, optical depth, and velocity dispersion, which are among the key drivers of α CO. The central 300 pc nuclei in both galaxies show strong enhancement of temperature T k ≳ 100 K and density cm−3. Assuming a CO-to-H2 abundance of 3 × 10−4, we derive 4-15 times lower α CO than the Galactic value across our maps, which agrees well with previous kiloparsec-scale measurements. Combining the results with our previous work on NGC 3351, we find a strong correlation of α CO with low-J 12CO optical depths (τ CO), as well as an anticorrelation with T k. The τ CO correlation explains most of the α CO variation in the three galaxy centers, whereas changes in T k influence α CO to second order. Overall, the observed line width and 12CO/13CO 2-1 line ratio correlate with τ CO variation in these centers, and thus they are useful observational indicators for α CO variation. We also test current simulation-based α CO prescriptions and find a systematic overprediction, which likely originates from the mismatch of gas conditions between our data and the simulations.
Veröffentlicht: 15. Juni 2023
Gesehen am 07.08.2023
Im Titel ist die Zahl 2 tiefgestellt